The doomscrolling during the COVID 19 pandemic in university students from Huancayo 2022 - Jesus Mallqui , Saul (2023)
Objective: to determine the prevalence of doomscrolling during the Covid 19 pandemic in university students from the province of Huancayo 2022, with the intention of analyzing, by extension, if doomscrolling as a habit is beginning to reduce mental health in university students from the city of Huancayo. Material and methods: The quantitative approach, scientific method, descriptive level, simple descriptive non-experimental design was used; we worked with a sample of 552 male and female students from five universities in the city of Huancayo. The instrument used was the Scale to evaluate Dommscrolling composed of 25 valid and reliable items. The theoretical foundation of the work was found in the periodical publication of scientific journals published in English. Results: it is evident that only 23.2% show an absence of doomscrolling indicators; prevalence of doomscrolling in women (80.9%) than in men (71.5%); prevalence is also observed in subjects between 20 and 22 years of age (79.4%). Conclusions: It was determined that 39.1% of the evaluated university students denote moderate and high levels of dommscrolling, while 21.7% of them denote the absence of indicators of this variable.